2020
DOI: 10.1002/acp.3628
|View full text |Cite
|
Sign up to set email alerts
|

The effect of varying danger controllability on attention to threat messages

Abstract: Summary The objective of this study is to determine whether attention toward fear messages is affected by variation in the controllability of the associated danger. There is no consensus regarding the effectiveness of fear appeals in driving adaptive behaviour, and it may be the case that threat messages fail to capture attention if the associated danger is not explicitly controllable. One hundred and sixty undergraduate university students completed a computer task that involved exposure to threat cues signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…Furthermore, a previous study found that smokers have a one-decade shorter life expectancy compared to nonsmokers (16), emphasising the need of raising knowledge about the impact of smoking among adolescents, thus smoking-related morbidity and mortality might be avoided at a younger age. In line with the previous finding which reports that knowing the negative impacts of the behaviour will prevent a person from continuing the behaviour (17,18) and it applies to smoking behaviour.…”
Section: Introductionsupporting
confidence: 91%
“…Furthermore, a previous study found that smokers have a one-decade shorter life expectancy compared to nonsmokers (16), emphasising the need of raising knowledge about the impact of smoking among adolescents, thus smoking-related morbidity and mortality might be avoided at a younger age. In line with the previous finding which reports that knowing the negative impacts of the behaviour will prevent a person from continuing the behaviour (17,18) and it applies to smoking behaviour.…”
Section: Introductionsupporting
confidence: 91%
“…This pattern of attention allocation is referred to as attentional bias alignment [ 31 ]. Several studies have now demonstrated that individuals in general indeed flexibly align their attentional bias to such variation in danger controllability, to show a greater attentional bias to threats signalling more controllable dangers relative to threats signalling less controllable dangers [ 31 , 34 ]. In the current study, we propose that a decreased ability to show such attentional bias alignment contributes to experiencing disruptive worry in particular.…”
Section: Introductionmentioning
confidence: 99%